Motor-Skill Learning Is Dependent on Astrocytic Activity - Ragunathan Padmashri; Anand Suresh; Michael D. Boska; Anna Dunaevsky (Neural Plasticity)
Motor-skill learning induces changes in synaptic structure and function in the primary motor cortex through the involvement of a long-term potentiation- (LTP-) like mechanism. Although there is evidence that calcium-dependent release of gliotransmitters by astrocytes plays an important role in synaptic transmission and plasticity, the role of astrocytes in motor-skill learning is not known. To test the hypothesis that astrocytic activity is necessary for motor-skill learning, we perturbed astrocytic function using pharmacological and genetic approaches. We find that perturbation of astrocytes either by selectively attenuating IP3R2 mediated astrocyte Ca2+ signaling or using an astrocyte specific metabolic inhibitor fluorocitrate (FC) results in impaired motor-skill learning of a forelimb reaching-task in mice. Moreover, the learning impairment caused by blocking astrocytic activity using FC was rescued by administration of the gliotransmitter D-serine. The learning impairments are likely caused by impaired LTP as FC blocked LTP in slices and prevented motor-skill training-induced increases in synaptic AMPA-type glutamate receptor in vivo. These results support the conclusion that normal astrocytic Ca2+ signaling during a reaching task is necessary for motor-skill learning.